A shift in education to instill and value sustainability - Cantú-Martínez, Pedro César (2020)
This theoretical review highlights the need to advocate a new type of development in order to ensure the continuity and harmony between human beings and their environment. This is why sustainability, as a concept that integrates economic, social and environmental aspects, will lead us to build values and attitudes that generate new lifestyles. Education is thus regarded as a social instrument that allows providing guidance for human behavior through the transmission of knowledge. Our objective was to become familiar with the topic at hand and highlight the role it plays in education, as well as educational institutions, so as to promote sustainability within the framework of the Sustainable Development Goals. In order to do so, we used an empirical-analytical methodological approach to outline that education is put forth as a humanization process that offers a new vision of the world and meaning of life. Therefore, educational institutions play an important role in providing a new meaning to symbolic and imaginary constructs and circumventing visions that are detrimental to the environment and ensuingly to human beings whose aim is to develop an environmentally literate citizenry through sustainability.